Metaphors and allusions to ancient writers and the Bible in Ioannis Apocaukos’ epistles relevant to medical and paramedical issues - Diamandopoulos, Athanasios (DELTOS, 2024)
Ioannis Apocaukos (1153/60 - 1235) was a famous Metropolitan of Naupactus, today a minor town in Southwestern Greece, but then one of the strongest Seats of the Orthodox Church in the Balkans. He was a prolific writer, and apart from many theological works he wrote extensively on political, social and medical matters. In the fashion of Byzantine epistolographers, he excelled in correspondence with numerous illustrious personalities of his area and era. A frequently recurring topic was his illness, described in a flamboyant language. In his letters, he used direct or indirect metaphors and allusions to passages from prominent religious or secular authors of antiquity. In this paper, we tried to trace the obscure threads joining his references to medical and paramedical issues with poets, historians, orators, philosophers and clergymen of the past. We identified nineteen and commented extensively upon them.